Generalized Serre Problem over Elementary Divisor Rings. (7th October 2015) - Zheng, Licui; Liu, Jinwang; Liu, Weijun
Abstract : Matrix factorization has been widely investigated in the past years due to its fundamental importance in several areas of engineering. This paper investigates completion and zero prime factorization of matrices over elementary divisor rings (EDR). The Serre problem and Lin-Bose problems are generalized to EDR and are completely solved.